Monocyte eukaryotic initiation factor 2 signaling differentiates 17-hydroxy-docosahexaenoic acid levels and pain - Peter R.W. Gowler; Asta Arendt-Tranholm; James Turnbull; Rakesh R. Jha; David Onion; Tony Kelly; Afroditi Kouraki; Paul Millns; Sameer Gohir; Susan Franks; David A. Barrett; Ana M. Valdes; et al. (iScience)
Summary: Our goal was to probe the potential transcriptomic basis for the relationship between plasma levels of the specialized pro-resolving precursor, 17-hydroxy-docosahexaenoic acid (17-HDHA) and chronic pain. Participants with osteoarthritis (average age of 62.3, 60% were female, n = 30) were stratified by levels of 17-HDHA and self-reported pain scores. RNAs from CD14++/CD16-/CD66b-/HLA-DR+ (classical) monocytes were sequenced and differentially expressed mRNAs were identified with DESeq2. QIAGEN ingenuity pathway analysis identified the top ranked canonical biological pathway to be eukaryotic initiation factor 2 (EIF2) signaling (lower activation level in the low 17-HDHA-high pain group compared to the high 17-HDHA-low pain group (Z score −3)), followed by EIF4 and P70S6K signaling pathways and mTOR signaling. Our approach provides insight into the biological pathways contributing to the association between 17-HDHA and chronic osteoarthritis (OA) pain, identifying EIF2 signaling, with known roles in osteoclast differentiation, OA pathology, and pain, as a potential downstream target.